2019
DOI: 10.1016/j.acclit.2019.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The information content of operations-related disclosures

Abstract: This study examines the information content of firms’ operations-related disclosures (ORDs) and the importance of these disclosures as an information source to stock markets relative to other commonly examined sources of information. I find that ORDs constitute a large portion of corporate press releases. These disclosures are associated with significant stock price reactions and trading volume. The stock price reactions to ORDs are greater than the reactions to 10-K/Q reports and are of similar magnitudes to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Noh et al (2019) observe that, since the regulatory change, 8‐Ks have become a substitute for management guidance and firms have come to rely more on them to convey general types of news, rather than primarily negative news. Ma (2019) estimates that 8‐Ks explain variations in quarterly returns to a similar degree as management earnings forecasts, 10‐K/Q filings, and operations‐related disclosures.…”
Section: Background Prior Studies and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Noh et al (2019) observe that, since the regulatory change, 8‐Ks have become a substitute for management guidance and firms have come to rely more on them to convey general types of news, rather than primarily negative news. Ma (2019) estimates that 8‐Ks explain variations in quarterly returns to a similar degree as management earnings forecasts, 10‐K/Q filings, and operations‐related disclosures.…”
Section: Background Prior Studies and Hypothesis Developmentmentioning
confidence: 99%
“…The aim of the requirement is to ensure that investors are promptly informed of material corporate events. Prior studies have concluded that, consistent with this purpose, non‐earnings 8‐Ks provide timely information that is material to investors (Lerman and Livnat 2010; McMullin et al 2019; Noh et al 2019) and explain variations in quarterly returns to a degree similar to other disclosures, such as management earnings forecasts (Ma 2019). The objective of this paper is twofold.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Merkley (2013) collects narrative R&D disclosures in 10‐K reports and shows that managers adjust R&D disclosures based on earnings performance to provide relevant information. Ma (2019) finds that investor reactions to operations‐related disclosures are larger in magnitude than their reactions to 10‐K/Q reports and 8‐K filings. Cao et al (2018) investigates how competition affects firm‐initiated product development‐related press releases.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies show that managers may use the tone of press releases to achieve personal benefits (Arslan-Ayaydin et al, 2016) or mislead the market about firm fundamentals (Huang et al, 2013). However, with the exceptions of Merkley (2013), Cao et al (2018) and Ma (2019), prior research mainly focuses on earnings press releases and has not examined large samples of disclosures about firms' actual activities. Merkley (2013) collects narrative R&D disclosures in 10-K reports and shows that managers adjust R&D disclosures based on earnings performance to provide relevant information.…”
mentioning
confidence: 99%